2021
DOI: 10.1371/journal.pone.0259630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary red grape pomace on growth performance, hematology, serum biochemistry, and meat quality parameters in Hy-line Silver Brown cockerels

Abstract: Red grape (Vitis vinifera L.) pomace’s (RGP) beneficial bioactive compounds could improve growth and meat quality traits in chickens and thus valorize RGP waste that is usually disposed in landfills to the detriment of the environment. This study investigated the effect of RGP inclusion in diets of Hy-line Silver Brown cockerels on physiological and meat quality responses. Five isonitrogenous and isocaloric diets were formulated by mixing a standard grower diet with RGP at 0 (G0), 15 (G15), 30 (G30), 45 (G45) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Contrary, Tariq et al ( 2014 ) observed no change in erythrocyte levels in 35-day-old Japanese quail, whose diets were supplemented with Aloe vera and clove ( Syzigium aromaticum ). Jonathan et al ( 2021 ) also observed linear increases in erythrocytes, MCH, and eosinophils when 45 g/kg of RGP was supplemented in diets of Hy-line silver-brown cockerels, further indicating that higher AVG doses in this study compromised erythrocyte counts. Positive quadratic effects were noted for MCH as the level of AVG increased, which is a measure of the average amount of hemoglobin present in the red blood cells (Schaer et al, 2013 ).…”
Section: Discussionsupporting
confidence: 63%
“…Contrary, Tariq et al ( 2014 ) observed no change in erythrocyte levels in 35-day-old Japanese quail, whose diets were supplemented with Aloe vera and clove ( Syzigium aromaticum ). Jonathan et al ( 2021 ) also observed linear increases in erythrocytes, MCH, and eosinophils when 45 g/kg of RGP was supplemented in diets of Hy-line silver-brown cockerels, further indicating that higher AVG doses in this study compromised erythrocyte counts. Positive quadratic effects were noted for MCH as the level of AVG increased, which is a measure of the average amount of hemoglobin present in the red blood cells (Schaer et al, 2013 ).…”
Section: Discussionsupporting
confidence: 63%
“…The antioxidant effects of GP, grape seed, and their extracts have been the topic of research, with the emphasis that these products have a high possibility of improving the shelf-life of animal products by mitigating lipid peroxidation [11,13,14,38,45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“… ADF, acid detergent fiber; TDF, total dietary fiber; NDF, neutral detergent fiber; SDF, soluble dietary fibe; ADL, acid detergent lignin; ND, not detected. Supporting literature: 1 Alameldin [ 55 ]; Atalay [ 56 ]; Beres et al [ 57 ]; Chikwanha et al [ 28 ]; Ebrahimzadeh et al [ 58 ]; Ebrahimzadeh et al [ 59 ]; Erinle et al [ 45 ]; Goñi et al [ 18 ]; Gülcü et al [ 60 ]; Gungor et al [ 44 ]; Hosseini-Vashan et al [ 61 ]; Jonathan and Mnisi [ 62 ]; Leal et al [ 29 ]; Llobera and Cañellas [ 63 ]; Mirzaei-Aghsaghali et al [ 64 ]; Pérez Cid et al [ 32 ]; Valiente et al [ 65 ]; Vlaicu et al [ 66 ]; Winkler et al [ 67 ]; Yi et al [ 68 ]. 2 García-Rodríguez et al [ 69 ]; Goñ et al [ 70 ]; Karaman et al [ 71 ]; Milićević et al [ 26 ]; Pérez Cid et al [ 32 ]; Spanghero et al [ 72 ]; Tangolar et al [ 73 ]; Tangolar et al [ 74 ]; Yokotsuka and Singleton [ 75 ].…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%
“… SFA, saturated fatty acids; MUFA, monounsaturated fatty acids; PUFA, polyunsaturated fatty acids; GAE, gallic acid equivalents; TAE, tannic acid equivalents; CE, catechin equivalents; ND, not detected. Supporting literature: 1 Alameldin [ 55 ]; Beres et al [ 57 ]; Bustamante et al [ 27 ]; Ebrahimzadeh et al [ 59 ]; Erinle et al [ 45 ]; Goñi et al [ 18 ]; Gülcü et al [ 60 ]; Gungor et al [ 44 ]; Hosseini-Vashan et al [ 61 ]; Jonathan and Mnisi [ 62 ]; Kasapidou et al [ 76 ]; Leal et al [ 29 ]; Llobera and Cañellas [ 63 ]; Pérez Cid et al [ 32 ]; Vlaicu et al [ 66 ]; Yi et al [ 68 ]. 2 Goñi et al [ 70 ]; Gülcü et al [ 60 ]; Gungor et al [ 20 ]; Iuga and Mironeasa [ 15 ]; Karaman et al [ 71 ]; Milićević et al [ 26 ]; Pérez Cid et al [ 32 ]; Silva et al [ 77 ]; Tangolar et al [ 73 ]; Yokotsuka and Singleton [ 75 ].…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%